Journal Club Insights: Case Studies on Generative AI in Biomedical Laboratory Science Education - Necip, Filis; Qvist, Camilla Christine (Tidsskriftet Læring og Medier (LOM), 2025)
This study explores the utilization of Generative Artificial Intelligence (GenAI) in Journal Club (JC) sessions within Biomedical Laboratory Science (BLS) education, using ChatPDF. Focusing on case studies of 6th semester students, our research combines observational and tracking methodologies to assess student engagement with ChatPDF. Guided by a conceptual framework comprising self-efficacy with agency, digital literacy, data use, and critical analysis, the study examines students’ interactions with ChatPDF across three JCs. This research utilizes sequential mixed methods design, incorporating data from surveys and interviews, gaining deeper insights into students’ experiences and perceptions regarding GenAI. Findings show that while some students strategically used ChatPDF to support comprehension, preparation, and discussion, others relied on it primarily for translation or surface-level understanding. High self-efficacy was associated with deeper engagement and autonomous use of the tool, whereas lower self-efficacy often led to limited or passive interaction. While this study shows that GenAI has the potential to assist students in overcoming educational challenges, it also sheds light on the pitfalls associated with over-reliance on GenAI, the need for preserving student agency, and the importance of ensuring ethical and meaningful learning experiences.